2020
DOI: 10.1186/s12885-020-07023-9
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-to-alkaline phosphatase ratio serves as a prognostic indicator in unresectable pancreatic ductal adenocarcinoma: a propensity score matching analysis

Abstract: Background: Recent evidence suggests that albumin-to-Alkaline Phosphatase Ratio (AAPR) functions as a novel prognostic marker in several malignancies. However, whether it can predict the prognosis of unresectable pancreatic ductal adenocarcinoma (PDAC) remains unclear. Herein, we seek to investigate this possibility by a propensity score matching (PSM) analysis. Methods: This was a retrospective cohort study in which 419 patients diagnosed with unresectable PDAC and receiving chemotherapy were recruited. Patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Moreover, higher ALP levels have been demonstrated to serve as a risk factor for lymph node metastasis in esophageal cancer [ 24 ], correlate with a later stage in colon cancer [ 25 ], and promote cell invasion and metastasis in pancreatic carcinoma; whereas, decreased ALP activity can reportedly inhibit tumor cell metastasis and invasion [ 26 ]. Other studies have indicated that the ratios of ALP to serum albumin and ALP to lactate dehydrogenase might predict the OS of patients with resectable and unresectable pancreatic carcinoma, respectively [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, higher ALP levels have been demonstrated to serve as a risk factor for lymph node metastasis in esophageal cancer [ 24 ], correlate with a later stage in colon cancer [ 25 ], and promote cell invasion and metastasis in pancreatic carcinoma; whereas, decreased ALP activity can reportedly inhibit tumor cell metastasis and invasion [ 26 ]. Other studies have indicated that the ratios of ALP to serum albumin and ALP to lactate dehydrogenase might predict the OS of patients with resectable and unresectable pancreatic carcinoma, respectively [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant reports have found that alkaline phosphatase (ALP) plays a major role in inflammation by affecting purine signal transduction, which can stop inflammatory signals and thus induce immunosuppression [ 10 ]. Furthermore, the predictive value of ALP combined with other biomarkers has been reported in resectable and nonresectable pancreatic carcinoma [ 11 13 ]. Additionally, in patients undergoing immunotherapy, higher cholesterol (CHO) levels are known to be associated with a better prognosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ALP-to-ALB ratio (APAR), a novel prognostic marker amalgamating ALP and ALB, has been proposed and exhibits promising prognostic value in various cancers and other diseases [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Moreover, APAR exhibits superior predictive performance for clinical outcomes when compared with independent ALP and ALB measurements [20].…”
Section: Introductionmentioning
confidence: 99%
“…And according to the clinical characteristics, AAV is categorized into three subtypes; microscopic polyangiitis, granulomatosis with polyangiitis, and eosinophilic granulomatosis with polyangiitis. 1,2 Central nervous system involvement of AAV is not a frequently observed systemic manifestation, and cerebrovascular accident (CVA) may occur in a minority of AAV patients. 3 As such, the low frequency of CVA involvement makes it difficult to predict and detect among AAV patients.…”
Section: Introductionmentioning
confidence: 99%